2021
DOI: 10.3390/foods10071638
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs Involved in the Therapeutic Functions of Noni (Morinda citrifolia L.) Fruit Juice in the Treatment of Acute Gouty Arthritis in Mice Induced with Monosodium Urate

Abstract: We investigated the functions of microRNAs in the therapeutic effects of noni (Morinda citrifolia L.) fruit juice on mouse models of acute gouty arthritis induced with monosodium urate (MSU). Compared with the model group (treated with MSU), mice in both the positive control group (treated with both MSU and colchicine) and noni fruit juice group (treated with MSU and noni fruit juice) showed a significantly decreased degree of paw swelling in 5 days, as well as the contents of two types of proinflammatory cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 78 publications
0
9
0
Order By: Relevance
“…In addition, like Tripterine (77), Total glucosides of paeony (78) and Epigallocatechin (57) were also reported to regulate the expression of miR-449a, miR-876, and miR-9, respectively, to alleviate the progression of GA. Similarly, Li, X et al reported that Noni (Morinda citrifolia L.) fruit Juice also modulates miRNA and pro-inflammatory factors to treat MSU-induced AGA in mice (108).…”
Section: Application Of Mirnas In Clinical Diagnosis and Treatment Of Gamentioning
confidence: 96%
See 1 more Smart Citation
“…In addition, like Tripterine (77), Total glucosides of paeony (78) and Epigallocatechin (57) were also reported to regulate the expression of miR-449a, miR-876, and miR-9, respectively, to alleviate the progression of GA. Similarly, Li, X et al reported that Noni (Morinda citrifolia L.) fruit Juice also modulates miRNA and pro-inflammatory factors to treat MSU-induced AGA in mice (108).…”
Section: Application Of Mirnas In Clinical Diagnosis and Treatment Of Gamentioning
confidence: 96%
“…Similarly, Li, X et al. reported that Noni (Morinda citrifolia L.) fruit Juice also modulates miRNA and pro-inflammatory factors to treat MSU-induced AGA in mice ( 108 ).…”
Section: Application Of Mirnas In Clinical Diagnosis and Treatment Of Gamentioning
confidence: 99%
“…Moreover, Li’s group found that miRNAs are also involved in the therapeutic effect of noni juice on AGA. They identified multiple miRNAs expressed abnormally in the colchicine and noni juice groups by modern sequencing techniques and hypothesized that these miRNAs are involved in the regulation of the pathogenesis of AGA in mice ( Li et al, 2021b ).…”
Section: Application Of Micrornas In the Treatment Of Gouty Arthritis...mentioning
confidence: 99%
“…TLR4 is a sensor for HMGB1 and LPS, molecules implicated in chronic fatigue, pain, and depression [267]. In addition, TLR4 alters efferocytosis and exacerbates Mycoplasma infections, suggesting that biological barriers could be enhanced by inhibiting this protein [268,269] (Table 1).…”
Section: Tlr4 Antagonistsmentioning
confidence: 99%